The investigation of the impacts of emotions on decision-making by means of event-related low beta oscillations - Yılmaz, Funda; Çiçek, Büşra; Çiçek, Yusuf; Aktürk, Tuba; Güntekin, Bahar (Wiley, 2020)
[Abstract Not Available]
Keywords: Emotions; Beta Oscillations; Investigation